Verbal Autopsy of Maternal Mortality in Rawalpindi District - Mahum Khizar; Aimen Hafeez; Ayesha Khan; Kinza Awais; Komal Rashid (Journal of Islamic International Medical College, 2022)
Objective: To identify the causes and risk factors leading to maternal mortality through verbal autopsy in the District of Rawalpindi, Pakistan. Study Design: A retrospective, descriptive study. Place and Duration of Study: The study was carried out in Community Department of Foundation University Medical College Islamabad from January 05, 2019, to December 25, 2019. Materials and Methods: Data of 105 women died of causes related to death during pregnancy/ delivery between 01 April 2013 and 30 April 2018 was retrieved from the office of District Health Officer (DHO) Rawalpindi. A Verbal Autopsy was conducted to determine cause of death and the possible risk factors, through a structured questionnaire that was filled by close relatives of the deceased women. Analysis of data was done using SPSS version 25.0. Results: The Mean age of the patients was 31 years, and it ranged from 15 to 49 years. In 26.7% of mothers cause of death could not be determined. Overall, the major and most obvious cause of maternal death was delivery related hemorrhage in 58% cases. Out of these, antepartum hemorrhage was the commonest cause occurring in 43.8% of the total cases. Postpartum hemorrhage occurred in 11.4% cases, while fatal hemorrhage during the delivery occurred in 2.8% mothers. Eclampsia was the next common cause that occurred in 11.4% mothers. Difficult and prolonged labour was found to be cause of death in 2.8% cases, while 0.95% died of Sepsis. Among the risk factors, lack of antenatal care emerged as the leading risk factor, present in 62% mothers, followed by anemia being present in 46.6% mothers. Multi-parity was found to be the next common risk factor being present in 26.6% mothers. Reduced interval in successive pregnancies was found in 21% cases. Systemic medical disorders like hypertension, renal disorders, Diabetes Mellitus, Pneumonia, hepatic failure, were found in 6.66% mothers. History of complications in previous pregnancies was present in 3.8% cases. History of lack of proper medical services in the hospital as possible factor leading to death was present in only 5 (4.8%) cases. Conclusion: Hemorrhage related with delivery, especially the antepartum hemorrhage emerged as the commonest cause of maternal mortality, followed by eclampsia. At the same time, lack of antenatal care and anaemia emerged as the commonest risk factors in this regard.